The Integrated Spatial Assessment of The Flood Hazard Using AHP-GIS: The Case Study of Gorontalo Regency - Muhammad Ramdhan Olii; Aleks Olii; Ririn Pakaya (Indonesian Journal of Geography, 2021)
Mapping of potential flood hazards is an important element in ensuring proper planning of development and implementing flood disaster mitigation efforts for flooded areas. Therefore, this study was conducted to assess the regional-scale flood hazard areas in Gorontalo District using an AHP-GIS integration technique with the focus on factors such as annual rainfall, elevation, slope, soil type, distance to the water bodies, and land-use. The flood hazard was divided into five classes, ranging from very low to very high, and 13.61% of the total area in Gorontalo Regency is classified as either high or very high. Moreover, the distribution of the hazard was verified and 65 events were recorded to have a level of 90.7% and this indicates the model is reliable to assess flood hazard. The results showed GIS-AHP integration is a promising method to accurately predict flood-hazard areas, especially in those with limited data.